Acute responsiveness to calcitonin in chronic renal failure. Issue 6032 (14th August 1976) - Cochran, M; Hillyard, C J; Dew, G J; Martin, T J
Abstract : The acute effect of porcine calcitonin was tested in 17 patients undergoing chronic haemodialysis. In normal adults calcitonin has no effect on plasma calcium or phosphate levels, but in nine patients both concentrations were substantially reduced after calcitonin. This hypocalcaemic and hypophosphataemic effect was a function of the initial plasma phosphate level but was unrelated to the initial plasma calcium level. Plasma hydroxyproline levels were not significantly different in the two groups an were unaffected by calcitonin. In 11 patients fasting plasma calcitonin levels were undetectable with an assay sensitive to 0-1 mug/1. Calcitonin seems to have an acute effect in chronic renal failure which may not operate by arresting bone resorption but is dependent on the plasma phosphate concentration.